Results in the Latin America and Caribbean Region, 2016, Volume 7 - World Bank (World Bank, Washington, DC, 2016)
Over the last decade, the countries of the Latin America and the Caribbean region experienced a deep economic and social transformation which lifted millions out of poverty and swelled the ranks of the middle class. Strong economic growth driven by both domestic reforms and a favorable global economic environment, was responsible for this progress. Complementary social programs, made possible by growing fiscal space, helped finance programs that supported the poor and disadvantaged. Economic tailwinds have now receded and much of the region is now working to hold on to the recent economic and social gains. Governments are having to adjust to the new global conditions which an increasing number of analysts are regarding as 'the new normal'. This means that the region will need to work harder to (i) revive economic growth through productivity gains and stable macroeconomic policies; (ii) invest in sustainable cities and infrastructure for an increasingly urban population; and (iii) help the poor get out of poverty through quality education and health services and affordable social protection programs.